Fluorosilane coupled layered double-metal hydroxide composite material, preparation method thereof and application of fluorosilane coupled layered double-metal hydroxide composite material in removal of perfluoroalkyl or polyfluoroalkyl substances in water
By introducing a fluorosilane coupling agent on the layered bimetal hydroxide surface to form a fluorosilane-coupled layered bimetal hydroxide composite material, the problem of insufficient adsorption selectivity and stability in the prior art is solved, and the problem of insufficient adsorption selection and stability is achieved Efficient removal of perfluoro or polyfluoroalkyl substances is suitable for water pollution treatment.
Patent Information
- Application Number
- CN202411564949.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-07
AI Technical Summary
When treating perfluoro or polyfluoroalkyl substances, the adsorption selectivity and stability are insufficient, making it difficult to effectively remove these stubborn pollutants.
By introducing a fluorosilane coupling agent on the surface of the layered bimetal hydroxide, a fluorosilane-coupled layered bimetal hydroxide composite is formed, and the adsorption performance is enhanced by fluoro-fluoro interaction and hydrophobic interaction, and room temperature conditions are used. Coupling reaction was performed.
It achieves excellent adsorption performance and stability of perfluoro or polyfluoroalkyl substances under different conditions, and maintains high adsorption performance after multiple uses, which is suitable for removing PFASs pollution in groundwater and industrial wastewater.
Smart Images

Figure CN119258992A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental protection and water treatment, and specifically relates to a fluorosilane coupled layered double metal hydroxide composite material, a preparation method thereof, and an application thereof in removing perfluoro or polyfluoroalkyl substances in water. Background Art
[0002] Layered double hydroxides (LDHs) are a class of inorganic materials with a layered structure, composed of divalent metal ions (such as Mg2 + ) and trivalent metal ions (such as Al3 + ) are connected by a hydrogen-oxygen bridge bond, and its general chemical formula is [M 2+ 1-x M 3+ x (OH)2][A n- ] x / n ·zH2O, of which M2 + and M 3+ Represent divalent and trivalent metal ions, An - The interlayer anions are exchangeable. This unique structure makes LDHs have broad application prospects in the fields of environmental remediation, catalysis, and drug release.
[0003] At present, LDHs have shown excellent performance in adsorbing pollutants in water. For example, LDHs can effectively remove anionic pollutants such as arsenate, chromate, phosphate and fluoride in water through ion exchange. Among them, per- and polyfluoroalkyl substances (PFASs) have extremely high thermal and chemical stability due to their unique carbon-fluorine bond structure, and are widely used in waterproof coatings, fire-fighting foams, textiles and food packaging. However, PFASs are difficult to degrade, are highly persistent in the environment, and have been shown to be potentially harmful to human health and ecosystems. However, when LDHs are used to treat stubborn pollutants such as PFASs, the selective adsorption capacity and adsorption stability of LDHs adsorbents for PFASs are still weak. Summary of the invention
[0004] The object of the present invention is to provide a fluorosilane-coupled layered double metal hydroxide composite material, a preparation method thereof, and an application of the composite material in removing perfluoro or polyfluoroalkyl substances in water. The fluorosilane-coupled layered double metal hydroxide composite material provided by the present invention exhibits excellent stability and excellent adsorption performance for PFASs under different coexisting anions, pH values, and ionic strength conditions; at the same time, the composite material can still maintain a high adsorption performance for PFASs after multiple uses.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The invention provides a fluorosilane coupled layered double metal hydroxide composite material, comprising a layered double metal hydroxide and a fluorosilane coupling agent chemically modified on the surface of the layered double metal hydroxide.
[0007] Preferably, the layered double metal hydroxide comprises a magnesium-aluminum layered double metal hydroxide.
[0008] Preferably, the fluorosilane coupling agent includes 1H,1H,2H,2H-perfluorooctyltriethoxysilane.
[0009] The present invention provides a method for preparing the fluorosilane coupled layered double metal hydroxide composite material described in the above technical solution, comprising the following steps:
[0010] The layered double metal hydroxide, alcohol solvent, fluorosilane coupling agent and catalyst are mixed to carry out coupling reaction to obtain the fluorosilane coupled layered double metal hydroxide composite material.
[0011] Preferably, the volume ratio of the layered double hydroxide to the fluorosilane coupling agent is 1 g: (0.1-0.6) mL.
[0012] Preferably, the alcohol solvent includes ethanol, the catalyst includes an organic acid, the coupling reaction temperature is room temperature, and the reaction time is 24 to 48 hours.
[0013] The present invention provides the use of the fluorosilane coupled layered double metal hydroxide composite material described in the above technical scheme or the fluorosilane coupled layered double metal hydroxide composite material prepared by the preparation method described in the above technical scheme in removing perfluoro or polyfluoroalkyl substances in water.
[0014] Preferably, the perfluoro or polyfluoroalkyl substance includes one or more of perfluorobutyric acid, perfluoropentanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, perfluorooctanoic acid, perfluorodecanoic acid, perfluorobutane sulfonic acid, perfluorohexane sulfonic acid, perfluorooctane sulfonic acid, 6:2 fluorosulfonic acid, perfluoroalkyl ether sulfonate and hexafluoropropylene oxide trimer acid.
[0015] Preferably, the pH value of the water body containing perfluoro or polyfluoroalkyl substances is 3 to 11; the ionic strength of the water body containing perfluoro or polyfluoroalkyl substances is 1 to 50 mM; the water body containing perfluoro or polyfluoroalkyl substances also contains coexisting ions, and the coexisting ions include one or more of nitrate ions, chloride ions, carbonate ions and sulfate ions.
[0016] Preferably, the application comprises the following steps: adding the fluorosilane coupled layered double metal hydroxide composite material to a water body containing perfluoro or polyfluoroalkyl substances for adsorption, thereby obtaining a water body from which the perfluoro or polyfluoroalkyl substances are removed and an adsorption-saturated fluorosilane coupled layered double metal hydroxide composite material;
[0017] The adsorption saturated fluorosilane coupled layered double metal hydroxide composite material is regenerated, and the regeneration is performed using a regeneration solution, and the regeneration solution includes methanol, NaCl and water.
[0018] The present invention provides a fluorosilane-coupled layered double hydroxide composite material (LDHs-FAS), comprising a layered double hydroxide and a fluorosilane coupling agent chemically modified on the surface of the layered double hydroxide. The present invention can effectively improve the adsorption performance of the obtained composite material on PFASs by modifying the surface of the layered double hydroxide with a fluorosilane coupling agent. The fluorosilane coupling agent has high hydrophobicity and can significantly enhance the selective adsorption capacity of LDHs on PFASs through fluorine-fluorine interaction and hydrophobic interaction. In addition, the fluorosilane-coupled layered double hydroxide composite material provided by the present invention exhibits excellent stability and adsorption performance under different coexisting anions, pH values and ionic strength conditions. The results of the regeneration cycle experiment show that the material can still maintain a high adsorption performance after multiple uses.
[0019] The present invention provides a method for preparing a fluorosilane-coupled layered double hydroxide composite material described in the above technical solution, comprising the following steps: mixing the layered double hydroxide, an alcohol solvent, a fluorosilane coupling agent and a catalyst for coupling reaction to obtain the fluorosilane-coupled layered double hydroxide composite material. The preparation method provided by the present invention does not require high temperature and high pressure, and only uses room temperature conditions to prepare high-purity and high-yield LDHs-FAS materials through coprecipitation and surface modification. The method is green and environmentally friendly, low in cost, and easy to industrialize. The prepared LDHs-FAS has excellent PFASs adsorption performance and is suitable for removing PFASs pollutants in groundwater and industrial wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Scanning electron microscope (SEM) images of the magnesium-aluminum layered double hydroxide (LDHs) and the magnesium-aluminum layered double hydroxide (LDHs-FAS) modified by fluorosilane coupling prepared in the examples; Figure 1 (a) is the SEM image of LDHs. Figure 1 (b) is the SEM image of LDHs-FAS; Figure 1 (c) in the figure is the contact angle analysis diagram of LDHs; Figure 1(d) in the figure is the contact angle analysis diagram of LDHs-FAS;
[0021] Figure 2 The structural characterization diagrams of LDHs and LDHs-FAS prepared in the examples; Figure 2 a in is: X-ray diffraction (XRD) spectrum, Figure 2 b in the figure is: Fourier transform infrared spectrum (FTIR) spectrum, Figure 2 c in is: Zeta potential measurement result, Figure 2 d in: thermogravimetric analysis (TGA) curve;
[0022] Figure 2-1 for Figure 2 Illustration in d in;
[0023] Figure 3 X-ray photoelectron spectroscopy (XPS) spectrum of LDHs-FAS prepared in Example; Figure 3 a in: XPS spectrum of Si 2p; Figure 3 b in the figure is: XPS spectrum of F 1s, Figure 3 c in the figure is: Mg 1s XPS spectrum, Figure 3 d in: XPS spectrum of Al 2p; Figure 3 e in: elemental analysis and full spectrum of LDHs-FAS;
[0024] Figure 4-1 This is a graph showing the adsorption performance of PFOS on LDHs-FAS in the examples; Figure 4-1 a in the figure is the effect of different FAS addition amounts on the adsorption of PFOS by LDHs-FAS. Figure 4-1 b in the figure is the effect of different FAS addition amounts on the adsorption of PFOA by LDHs-FAS;
[0025] Figure 4-2 This is a graph showing the adsorption performance of PFOS on LDHs-FAS in the examples; Figure 4-2 a in the figure is the optimal dosage research result of LDHs-FAS adsorption of PFOS. Figure 4-2 b in the figure is the adsorption kinetics curve of PFOS. Figure 4-2 c in: PFOS adsorption isotherm and fitting results;
[0026] Figure 5 The adsorption and removal efficiency of PFOS by LDHs-FAS under different environmental conditions in the examples; Figure 5 a in the figure is the adsorption and removal efficiency of PFOS by LDHs-FAS under different pH conditions. Figure 5 b in the figure is the adsorption and removal efficiency of PFOS by LDHs-FAS under different ionic strength conditions. Figure 5 c in the figure is the adsorption and removal efficiency of PFOS by LDHs-FAS under different coexisting anions (such as chloride, nitrate, sulfate and carbonate);
[0027] Figure 6 This is a diagram showing the removal effect of the LDHs-FAS prepared in the example on the PFASs mixture;
[0028] Figure 7 This is a graph showing the regeneration and reuse performance of LDHs-FAS prepared in the example; Figure 7 a in the figure is a comparison of the effects of regenerating LDHs-FAS saturated with PFOS using mixed solutions of methanol and NaCl at different concentrations. Figure 7 b in the graph is the adsorption performance of LDHs-FAS for PFOS in three adsorption-desorption cycles. DETAILED DESCRIPTION
[0029] The invention provides a fluorosilane coupled layered double metal hydroxide composite material, comprising a layered double metal hydroxide and a fluorosilane coupling agent chemically modified on the surface of the layered double metal hydroxide.
[0030] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0031] The fluorosilane coupled layered double metal hydroxide composite material provided by the present invention comprises a layered double metal hydroxide. In the present invention, the layered double metal hydroxide preferably comprises a magnesium-aluminum layered double metal hydroxide.
[0032] The fluorosilane coupled layered double hydroxide composite material provided by the present invention comprises a fluorosilane coupling agent chemically modified on the surface of the layered double hydroxide. In the present invention, the fluorosilane coupling agent preferably comprises 1H,1H,2H,2H-perfluorooctyltriethoxysilane. The chemical modification is preferably covalent bond modification.
[0033] In the fluorosilane-coupled layered double hydroxide composite material provided by the present invention, the fluorosilane coupling agent is present on the layered double hydroxide by surface modification rather than interlayer intercalation, and the fluorosilane coupling agent is uniformly distributed on the surface of the layered double hydroxide. The present invention introduces the fluorosilane coupling agent to the surface of LDHs through covalent bonds, thereby overcoming the problem of insufficient stability of traditional LDHs in complex environmental matrices, especially when organic solvents are used for adsorbent regeneration. The introduction of the fluorosilane coupling agent coordinates electrostatic interactions through fluorine-fluorine interactions and hydrophobic interactions, significantly enhancing the selective adsorption capacity of LDHs for PFASs.
[0034] The present invention provides a method for preparing the fluorosilane coupled layered double metal hydroxide composite material described in the above technical solution, comprising the following steps:
[0035] The layered double metal hydroxide, alcohol solvent, fluorosilane coupling agent and catalyst are mixed to carry out coupling reaction to obtain the fluorosilane coupled layered double metal hydroxide composite material.
[0036] In the present invention, the preparation method of the layered double metal hydroxide is preferably a high supersaturation coprecipitation method. The preparation method of the layered double metal hydroxide preferably comprises the following steps: dissolving the first metal salt and the second metal salt in water to obtain a mixed metal salt solution; dropping the mixed metal salt solution into an inorganic strong alkali aqueous solution, and performing a coprecipitation reaction under the condition of a pH value of ≥10 to obtain a suspension; and performing static aging on the suspension, and the solid phase obtained after solid-liquid separation is the layered double metal hydroxide.
[0037] The present invention dissolves the first metal salt and the second metal salt in water to obtain a mixed metal salt solution. In the present invention, the first metal salt is preferably a magnesium salt, and specifically preferably magnesium nitrate hexahydrate (Mg(NO3)2·6H2O); the second metal salt is preferably an aluminum salt, and specifically preferably aluminum nitrate nonahydrate (Al(NO3)3·9H2O); the molar ratio of the first metal salt and the second metal salt is preferably (1-6):1. The present invention has no special requirements for the amount of water used, and it is sufficient to ensure that the first metal salt and the second metal salt are completely dissolved.
[0038] After obtaining the mixed metal salt solution, the present invention drips the mixed metal salt solution into an inorganic strong alkali aqueous solution, performs a coprecipitation reaction under the condition of pH value ≥ 10, and obtains a suspension. In the present invention, the inorganic strong alkali aqueous solution is preferably a NaOH aqueous solution. The molar concentration of the inorganic strong alkali aqueous solution is preferably 2 mol / L. The volume ratio of the mixed metal salt solution and the inorganic strong alkali aqueous solution is preferably 1:1. The dripping speed is preferably 0.5 to 2 mL / min. The coprecipitation reaction is carried out under stirring. The temperature of the coprecipitation reaction is preferably room temperature.
[0039] After obtaining the suspension, the present invention subjects the suspension to static aging, and the solid phase obtained after solid-liquid separation is the layered double metal hydroxide. In the present invention, the temperature of the static aging is preferably room temperature, and the time is preferably 24 to 48 hours. The solid-liquid separation is preferably centrifugal separation. The solid-liquid separation is preferably centrifugal separation. After the solid-liquid separation obtains the solid phase product, it is preferably further included: washing and drying the solid phase product in sequence to obtain the layered double metal hydroxide (LDHs). The water washing is preferably ultrapure water washing. The water washing is preferably multiple water washings. The water washing is preferably until there is no NO3 in the washing liquid- The drying is preferably freeze drying.
[0040] In the present invention, the alcohol solvent preferably includes ethanol. The catalyst preferably includes an organic acid, and the organic acid is preferably acetic acid. The volume ratio of the mass of the layered double hydroxide to the fluorosilane coupling agent is preferably 1g: (0.1-0.6) mL, and is specifically preferably 1g: 0.1 mL, 1g: 0.2 mL, 1g: 0.4 mL, or 1g: 0.6 mL. The present invention has no special requirements for the amount of the alcohol solvent and the catalyst, as long as the coupling reaction is carried out smoothly. The temperature of the coupling reaction is preferably room temperature, and the time is preferably 24-48 hours. The coupling reaction is preferably carried out under stirring. In the present invention, after the coupling reaction is completed, a coupling reaction liquid is obtained. The present invention preferably separates the coupling reaction liquid into solid and liquid, and the obtained solid phase product is washed and dried in sequence to obtain the fluorosilane coupled layered double hydroxide composite material (LDHs-FAS). The solid-liquid separation is preferably centrifugal separation. The washing preferably includes: ethanol washing and water washing in sequence, and the number of ethanol washings is preferably 3 times, and the number of water washings is preferably 3 times. The drying is preferably freeze-drying.
[0041] The present invention provides the use of the fluorosilane coupled layered double metal hydroxide composite material described in the above technical scheme or the fluorosilane coupled layered double metal hydroxide composite material prepared by the preparation method described in the above technical scheme in removing perfluoro or polyfluoroalkyl substances in water.
[0042] The fluorosilane-coupled layered double hydroxide composite material (LDHs-FAS) provided by the present invention can efficiently adsorb PFASs under different pH values, ionic strengths and coexisting anion conditions, and has good regeneration performance.
[0043] In the present invention, the perfluoro or polyfluoroalkyl substance preferably includes one or more of perfluorobutyric acid, perfluoropentanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, perfluorooctanoic acid, perfluorodecanoic acid, perfluorobutane sulfonic acid, perfluorohexane sulfonic acid, perfluorooctane sulfonic acid, 6:2 fluorosulfonic acid, perfluoroalkyl ether sulfonate and hexafluoropropylene oxide trimer acid. The fluorosilane-coupled magnesium aluminum layered double hydroxide (LDHs-FAS) has a good removal rate for different types of perfluoro or polyfluoroalkyl substances in the water body. When the number of perfluoro or polyfluoroalkyl substances in the water body containing perfluoro or polyfluoroalkyl substances is greater than or equal to 2, the fluorosilane-coupled magnesium aluminum layered double hydroxide (LDHs-FAS) has a good removal rate for different types of perfluoro or polyfluoroalkyl substances in the water body.
[0044] In the present invention, the pH value of the water containing perfluoro or polyfluoroalkyl substances is preferably 3 to 11, more preferably 6 to 11, and further preferably 6 to 8. The ionic strength in the water containing perfluoro or polyfluoroalkyl substances is preferably 1 to 50 mM. The ionic strength in the water containing perfluoro or polyfluoroalkyl substances is specifically the molar concentration of NaNO3 in the water containing perfluoro or polyfluoroalkyl substances. The water containing perfluoro or polyfluoroalkyl substances preferably also contains coexisting ions, and the coexisting ions include one or more of nitrate ions, chloride ions, carbonate ions and sulfate ions.
[0045] In the present invention, the application preferably includes the following steps: adding the fluorosilane coupled layered double metal hydroxide composite material to a water body containing perfluoro or polyfluoroalkyl substances for adsorption, and obtaining a water body from which perfluoro or polyfluoroalkyl substances are removed and a saturated fluorosilane coupled layered double metal hydroxide composite material. The mass concentration of each perfluoro or polyfluoroalkyl substance in the water body containing perfluoro or polyfluoroalkyl substances is preferably 0 to 350 mg / L, and is not 0, and is specifically preferably 200 μg / L to 1 mg / L, and is specifically preferably 200 μg / L or 1 mg / L. After the fluorosilane coupled layered double metal hydroxide composite material is added to the water body containing perfluoro or polyfluoroalkyl substances, the mass concentration of the fluorosilane coupled layered double metal hydroxide composite material in the water body is preferably 0.1 to 1 g / L, and is more preferably 0.25 to 0.5 g / L. The time for adsorption to saturation is preferably 5 min to 24 h, and is specifically preferably 5 min or 20 min.
[0046] After the saturated fluorosilane coupled layered double metal hydroxide composite material is adsorbed, the present invention regenerates the saturated fluorosilane coupled layered double metal hydroxide composite material, and the regeneration is performed using a regeneration solution, and the regeneration solution includes methanol, NaCl and water.
[0047] In the present invention, the mass percentage of formaldehyde in the regeneration solution is preferably 50-70%, specifically preferably 50%, 60% or 70%; the mass percentage of NaCl is preferably 1wt%. The regeneration time is preferably 12h, and the regeneration temperature is preferably 25°C.
[0048] The present invention relates to a preparation method and application of a magnesium-aluminum layered double hydroxide composite silane coupling agent, aiming to provide a material for efficiently adsorbing perfluorinated and polyfluoroalkyl substances (PFASs) in water. Specifically, the following steps are included: first, magnesium salt and aluminum salt are dissolved in water to prepare a metal salt solution, and magnesium-aluminum layered double hydroxides (LDHs) are prepared by a high supersaturation coprecipitation method; then LDHs are dispersed in ethanol, and a fluorosilane coupling agent and a small amount of acetic acid are added for modification to obtain fluorosilane-coupled modified magnesium-aluminum layered double hydroxides (LDHs-FAS). The structure and surface functional groups of LDHs-FAS are characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and other methods. The results show that the introduction of fluorosilane coupling agents significantly improves the hydrophobicity and thermal stability of the material. Experiments show that LDHs-FAS exhibits excellent PFOS selective adsorption performance under different pH values, ionic strengths and coexisting anion conditions, and its maximum adsorption capacity can reach 1530.33 mg / g. In addition, LDHs-FAS can still maintain stable adsorption performance in multiple adsorption-desorption cycles and has good regeneration ability. At the same time, the adsorbent material has a good removal effect on 11 PFASs. The present invention provides an efficient, economical and environmentally friendly water treatment material suitable for the adsorption and removal of PFASs in groundwater and industrial wastewater.
[0049] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0050] The raw materials used in the following examples include:
[0051] Perfluorobutyric acid (PFBA), perfluoropentanoic acid (PFPeA), perfluorohexanoic acid (PFHxA), perfluorooctanoic acid (PFOA), perfluorodecanoic acid (PFDA), perfluorobutane sulfonic acid (PFBS), perfluorohexane sulfonic acid (PFHxS), perfluorooctane sulfonic acid (PFOS), 6:2 fluoro-tween sulfonic acid (6:2FTS), perfluoroalkyl ether sulfonate (F-53B) and hexafluoropropylene oxide trimer acid (HFPO-TA). Magnesium nitrate hexahydrate (Mg(NO3)2·6H2O), aluminum nitrate nonahydrate (Al(NO3)3·9H2O), sodium hydroxide (NaOH), nitric acid (HNO3), potassium hydroxide (KOH), sodium nitrate (NaNO3), sodium sulfate (Na2SO4), sodium chloride (NaCl) and sodium carbonate (Na2CO3).
[0052] Example 1: Preparation of magnesium-aluminum layered double hydroxides (LDHs)
[0053] Raw materials preparation:
[0054] Magnesium nitrate hexahydrate (Mg(NO3)2·6H2O)
[0055] Aluminum nitrate nonahydrate (Al(NO3)3·9H2O)
[0056] 2M NaOH solution
[0057] Ultrapure water
[0058] Preparation steps:
[0059] 0.75 mol of magnesium nitrate hexahydrate and 0.25 mol of aluminum nitrate nonahydrate were dissolved in ultrapure water to prepare a metal salt solution with a total volume of 1 liter and a metal molar ratio of 3:1.
[0060] The metal salt solution was slowly added to 1 liter of 2M NaOH solution at a rate of 10 drops / min while stirring to maintain the pH value of the solution above 10.
[0061] The resulting white suspension was allowed to stand for 24 hours and centrifuged to obtain a white solid precipitate.
[0062] Wash the precipitate with ultrapure water several times until there is no NO3 in the washing liquid. - , and then the sample was dried in a freeze dryer to obtain magnesium-aluminum layered double hydroxides (LDHs).
[0063] Preparation of LDHs modified with fluorosilane coupling agent (LDHs-FAS)
[0064] Raw materials preparation:
[0065] LDHs prepared in Example 1
[0066] Ethanol
[0067] 1H,1H,2H,2H-Perfluorooctyltriethoxysilane (FAS)
[0068] acetic acid
[0069] Preparation steps:
[0070] Disperse 1 g of LDHs in 10 ml of ethanol and stir well.
[0071] To the above mixture, 0.1 ml of FAS and a few drops of acetic acid were added, with acetic acid serving as a catalyst.
[0072] The reaction was stirred at room temperature for 24 hours.
[0073] After the reaction was completed, the solid product was obtained by centrifugation and washed three times with ethanol and ultrapure water respectively.
[0074] The washed product was dried in a freeze dryer to obtain fluorosilane-coupled modified magnesium aluminum layered double hydroxide (LDHs-FAS).
[0075] Test Example 1: Characterization of LDHs-FAS
[0076] Structural characterization:
[0077] The crystal structures of LDHs and LDHs-FAS were analyzed by X-ray diffraction (XRD), confirming that the introduction of fluorosilane coupling agent did not significantly change the interlayer spacing of LDHs.
[0078] Fourier transform infrared spectroscopy (FTIR) was used to analyze the surface functional groups of LDHs and LDHs-FAS, and the characteristic peaks of CH bonds and Si-O bonds were detected.
[0079] X-ray photoelectron spectroscopy (XPS) was used to analyze the surface elemental composition and chemical state of LDHs-FAS to confirm the successful introduction of FAS.
[0080] Scanning electron microscopy (SEM) was used to observe the morphology of LDHs and LDHs-FAS to verify the uniform distribution of the fluorosilane coupling agent.
[0081] The water contact angles of LDHs and LDHs-FAS were measured using a contact angle tester to evaluate the changes in their hydrophilicity and hydrophobicity.
[0082] Thermogravimetric analysis:
[0083] The thermal decomposition behavior of LDHs and LDHs-FAS was measured by thermogravimetric analyzer (TGA) to analyze their thermal stability.
[0084] Test Example 2: PFOS Adsorption Performance of LDHs-FAS
[0085] Adsorption experiment:
[0086] In a 50 ml polypropylene centrifuge tube, 40 ml of 1 mg / L PFOS solution was added, and different doses of LDHs-FAS adsorbent (0.1 g / L to 1 g / L) were added, and the tube was shaken at 25° C. and 150 rpm for 24 hours.
[0087] The sample was taken with a disposable syringe, and after removing the initial 3.5 ml of solution, the residual concentration of PFOS was determined and the removal rate of the adsorbent was calculated.
[0088] The effects of different pH values (3-11), ionic strength (0-50 mM NaNO3) and coexisting anions (chloride, nitrate, sulfate and carbonate) on the adsorption of PFOS were studied.
[0089] Adsorption kinetics and isotherms:
[0090] Adsorption kinetics experiments were performed to determine the adsorption amount of PFOS on LDHs-FAS at different time points (0 to 60 minutes).
[0091] Adsorption isotherm experiments were conducted to determine the adsorption amount of PFOS at different initial concentrations (0-350 mg / L). Langmuir and Freundlich models were used for fitting to calculate the adsorption capacity and adsorption constant.
[0092] Test Example 3: Regeneration of LDHs-FAS
[0093] Regeneration experiment:
[0094] The PFOS-saturated LDHs-FAS was regenerated with mixed solutions of methanol and 1% NaCl of different concentrations (50% methanol-1% NaCl, 60% methanol-1% NaCl, 70% methanol-1% NaCl) and shaken at 25°C for 12 hours.
[0095] Compare the regeneration effects of different regeneration solutions and select the best regeneration solution.
[0096] The above adsorption and regeneration process was repeated three times to evaluate the recycling performance of LDHs-FAS.
[0097] From the above examples, it can be seen that the fluorosilane-coupled modified magnesium aluminum layered double hydroxide (LDHs-FAS) provided by the present invention has excellent performance in adsorbing PFASs, and exhibits good stability and regeneration performance under different environmental conditions, providing an efficient, economical and environmentally friendly solution to the problem of PFASs pollution.
[0098] Results and Discussion
[0099] Characterization of Fluorosilane-Coupling Modified Magnesium-Aluminum Layered Double Hydroxides (LDHs-FAS)
[0100] The fluorosilane-coupled magnesium-aluminum layered double hydroxides (LDHs-FAS) proposed in this invention show excellent performance in the adsorption of per- and polyfluoroalkyl substances (PFASs). The following is a detailed description of the main results and discussions.
[0101] 1. Structure and surface functional group characterization
[0102] Scanning electron microscopy (SEM) analysis
[0103] Figure 1 Scanning electron microscope (SEM) images of the magnesium-aluminum layered double hydroxide (LDHs) and the magnesium-aluminum layered double hydroxide (LDHs-FAS) modified by fluorosilane coupling prepared in the examples; Figure 1 (a) is the SEM image of LDHs. Figure 1 (b) in the figure is the SEM image of LDHs-FAS. Figure 1 (a) and Figure 1 (b) in the figure shows the SEM images of unmodified LDHs and modified LDHs-FAS respectively. The SEM image shows that the surface of the modified LDHs-FAS is relatively smooth and uniform, and the uniform distribution of the fluorosilane coupling agent is verified. The unmodified LDHs present a typical layered structure, while the modified LDHs-FAS shows obvious surface modification characteristics. The fluorosilane coupling agent is modified on the surface of the LDHs layer. The fluorosilane coupling agent will dehydrate and condense in ethanol. The fluorosilane coupling agent will replace the hydroxyl groups on the LDHs layer and then graft them in the form of covalent bonds. The XRD graph shows that the layered structure is still retained, and the fluorosilane coupling agent is modified on the surface of the LDHs.
[0104] Figure 1 (c) is the contact angle analysis diagram of LDHs, which shows that it is highly hydrophilic and the water contact angle is close to 0°. Figure 1 (d) is the contact angle analysis diagram of LDHs-FAS, showing its hydrophobicity after modification with fluorosilane coupling agent, and the water contact angle increases to 36.54°
[0105] Contact angle test
[0106] The water contact angle test results of unmodified LDHs and modified LDHs-FAS. The water contact angle of LDHs is close to 0°, indicating its high hydrophilicity. The water contact angle of the modified LDHs-FAS increased to 36.54°, significantly improving its hydrophobicity. This enhanced hydrophobicity helps to improve its adsorption capacity for hydrophobic PFOS molecules.
[0107] X-ray diffraction (XRD) analysis
[0108] Figure 2 The structural characterization diagrams of LDHs and LDHs-FAS prepared in the examples; Figure 2 Figure a in the figure is: X-ray diffraction (XRD) spectrum, Figure 2 Figure b in the middle is: Fourier transform infrared spectrum (FTIR) spectrum, Figure 2 Figure c in the figure is: Zeta potential measurement results, Figure 2 Figure d in the figure is the thermogravimetric analysis (TGA) curve.
[0109] Figure 2Figure a shows the XRD patterns of unmodified LDHs and modified LDHs-FAS. The XRD patterns show that the introduction of the fluorosilane coupling agent did not significantly change the interlayer spacing of LDHs, indicating that the crystal structure of LDHs remained stable during the modification process. Unmodified LDHs showed characteristic peaks at 2θ=11.5°, 23.1°, and 34.6°, while the characteristic peaks of modified LDHs-FAS at the same positions remained unchanged. This indicates that the fluorosilane coupling agent exists on LDHs by surface modification rather than interlayer intercalation.
[0110] Fourier transform infrared spectroscopy (FTIR) analysis
[0111] Figure 2 Figure b shows the FTIR spectra of unmodified LDHs and modified LDHs-FAS. LDHs-FAS has a wavelength of 2885-2975 cm -1 The stretching vibration peak of the CH bond appears in the range of 1064cm -1 The characteristic peaks of Si-O bonds appeared at 3400 cm -1 There is a broad peak at , which is attributed to the vibration of OH bonds, while in LDHs-FAS, the intensity of this peak is reduced, indicating the enhancement of hydrophobicity.
[0112] Figure 2 Figure c shows the Zeta potential measurement results of unmodified LDHs and modified LDHs-FAS. At pH 7, the Zeta potential of unmodified LDHs is +24.44mV, while the Zeta potential of modified LDHs-FAS decreases to +21.19mV. This indicates that the introduction of fluorosilane coupling agent does not change the surface positive charge properties of LDHs.
[0113] Thermogravimetric analysis (TGA)
[0114] Figure 2Figure d shows the TGA curves of unmodified LDHs and modified LDHs-FAS. Both materials dehydrate from room temperature to about 200 °C, including the evaporation of adsorbed water at about 100 °C and the elimination of interlayer crystallization water at about 200 °C. The weight loss between 200 °C and 400 °C is due to the simultaneous dehydroxylation and deionization reactions. It is worth noting that the weight loss of LDHs-FAS is slower below 350 °C because water is consumed by FAS grafting onto the LDHs surface and the -OH groups are consumed when Si-OH on the surface of -LDHs forms -Si-O-Mg or -Si-O-Al. In addition, LDHs-FAS exhibits a higher weight loss rate below 500 °C, which is attributed to the decomposition of functional groups in LDHs-FAS. The weight loss of LDHs above about 500 °C becomes negligible, indicating the formation of stable final products such as mixed metal oxides. In contrast, LDH-CF showed a slight weight loss at 550°C and 750°C, which may be due to the complex thermal decomposition of polyfluoroalkyl groups. At 800°C, the carbonization rate of LDHs-FAS was 50.94%, which was higher than that of LDHs (50.18%), which was consistent with the XPS analysis results, further proving that FAS was successfully loaded on the surface of LDHs. X-ray photoelectron spectroscopy (XPS) analysis
[0115] Figure 3 X-ray photoelectron spectroscopy (XPS) spectrum of LDHs-FAS prepared in Example; Figure 3 a in it is: elemental analysis and full spectrum of LDHs-FAS; Figure 3 b in the figure is: XPS spectrum of F 1s, Figure 3 c in the figure is: Mg 1s XPS spectrum, Figure 3 d in the figure is the XPS spectrum of Al 2p.
[0116] The XPS spectrum of LDHs-FAS shows that the binding energy of N 1s is 406 eV, corresponding to NO3 - . Si 2p (such as Figure 3 a) and F1s (such as Figure 3 The binding energies of (a) and (b) are 101.2 eV and 692.1 eV, respectively, indicating that FAS is successfully anchored on the LDHs surface. In the Si 2p spectrum, the peaks at 101.2 eV correspond to the binding energies of Si-C, respectively. These findings indicate that FAS is formed by the reaction of Si-OH with the hydroxyl groups on the LDHs layer, and that FAS exists on the LDHs surface in the form of covalent bonds. In summary, the preparation of LDHs-FAS material is successful.
[0117] 2. Thermal stability analysis
[0118] 3. Study on adsorption performance
[0119] Adsorption experiments
[0120] Figure 4-1 and Figure 4-2 This is a graph showing the adsorption performance of PFOS on LDHs-FAS in the examples; Figure 4-1 a in the figure represents the effect of different FAS addition amounts on the adsorption of PFOS by LDHs-FAS. Figure 4-1 b in the figure represents the effect of different FAS addition amounts on the adsorption of PFOA by LDHs-FAS. Figure 4-2 a in the figure is the optimal dosage research result of LDHs-FAS adsorption of PFOS. Figure 4-2 b in the figure is the adsorption kinetics curve of PFOS. Figure 4-2 c in the figure is: adsorption isotherm and fitting results of PFOS.
[0121] Figure 4-1 a and Figure 4-1 Figure b shows the effect of the amount of added FAS on the ability of LDHs-FAS adsorbent to remove PFOS and PFOA from water and compares it with the performance of pristine LDHs. After determining the optimal FAS addition amount of 1 mL / g (FAS / LDHs), LDHs-FAS composites were synthesized. Figure 4-1 a and Figure 4-1 As shown in b, among the four LDHs with different fluorine contents, the adsorption of PFOS and PFOA was enhanced to a certain extent. At the same time, the fluorination modification ratio also affected the dispersibility of LDHs in water. Fluorinated LDHs tend to accumulate nano-sized bubbles, and long-chain PFASs may adhere to the surface of these bubbles, which is another major reason for their effective adsorption. In view of the outstanding performance of LDHs-FAS in removing PFOS, its adsorption capacity was further studied. The study evaluated the effect of different LDHs-FAS adsorbent dosages on the removal of PFOS in 1000 ng / L aqueous solution. Figure 4-2 The data in a show that with the increase of LDHs-FAS addition, the removal rate of PFOS also increases, reaching a peak at an adsorbent dosage of 0.5 g / L. However, considering the cost of the adsorbent and the removal efficiency of PFOS, a LDHs-FAS dosage of 0.25 g / L was selected for subsequent experiments.
[0122] Figure 4-2Figure b compares the adsorption kinetics of PFOS by LDHs and fluorinated LDHs-FAS. In the initial stage of adsorption, both materials adsorb PFOS very quickly, and the adsorption capacity increases rapidly. Then the adsorption rate gradually slows down until equilibrium is reached. Within 1 hour of adsorption, the amount of PFOS adsorbed on LDHs and LDHs-FAS is 3.74 mg / g and 3.92 mg / g, respectively. In contrast, the adsorption rate and equilibrium adsorption capacity of LDHs are significantly lower than those of fluorinated LDHs-FAS. Specifically, under the experimental conditions, LDHs-FAS and LDHs reach adsorption equilibrium within 5 minutes and 20 minutes, respectively. The PFOS adsorption kinetics of the two materials were analyzed using pseudo-first-order and pseudo-second-order kinetic models, and the fitting parameters are shown in Table 1. The fitting results of the pseudo-second-order model are better than those of the pseudo-first-order model, R 2 are 0.993 and 0.996, respectively, indicating that the adsorption of PFOS onto LDHs is mainly chemical adsorption. However, the pseudo-first-order model also shows a significant R 2 values (0.977 and 0.978), indicating that physical adsorption also plays a role. It should be noted that the adsorption kinetics may be affected by multiple factors, such as adsorbent concentration, adsorbent loading, and water chemical parameters. Compared with the original LDHs, the fluorinated LDHs exhibited faster adsorption kinetics, indicating that the modification of fluoroalkylsilane functional groups created more favorable conditions for the adsorption of PFOS, which may be due to the change in the surface properties of LDHs that enhanced the interaction with PFOS. The adsorption kinetics of LDHs-FAS are also much faster than those of various adsorbents reported in previous studies, such as powdered activated carbon (PAC), granular activated carbon (GAC), ion exchange resins, fluorinated clays, and metal-organic frameworks (MOFs), which have adsorption equilibrium times for PFOS ranging from one hour to several days.
[0123] Table 1 Calculation parameters of pseudo-first-order and pseudo-second-order adsorption models of PFOS on LDHs and LDHs-FAS
[0124]
[0125] a Pseudo-first-order kinetic model: qt=qe(1-e (-k 1t))
[0126] b Pseudo-second-order kinetic model: t / qt=1 / (k2qe2)+t / qe
[0127] Figure 4-2Figure c shows the adsorption isotherms of LDHs and fluorinated LDHs-FAS for PFOS, which clearly shows that the maximum adsorption capacity of LDHs-FAS is much higher than that of LDHs. The adsorption isotherms of the two materials were fitted using the Langmuir and Freundlich models, and the results are shown in Table 2. The data in Table 2 show that the Langmuir model can better describe the adsorption process of PFOS on these materials. The adsorption capacities of LDHs and LDHs-FAS are 831.79 mg / g and 1530.33 mg / g, respectively, the latter far exceeding most reported adsorbents. Some researchers believe that a better fit of the Freundlich model usually indicates a tendency towards multilayer adsorption, while a better fit of the Langmuir model indicates monolayer adsorption. In the present invention, the adsorption of PFOS by fluorinated LDHs-FAS may involve both monolayer and multilayer mechanisms, because both models show a high fitting R 2 However, inferring whether the adsorption is monolayer or multilayer based on the isotherms is a simplification and needs to be further explored through other mechanistic studies.
[0128] Table 2 Calculation parameters of Langmuir and Freundlich models for PFOS adsorption on LDHs and LDHs-FAS
[0129]
[0130] a Langmuirmodel:qe=qmCe / (1 / b+Ce)
[0131] b Freundlichmodel:qe=KfCe1 / n
[0132] To investigate why fluorinated LDHs exhibited stronger adsorption capacity than non-fluorinated LDHs, the unique adsorption behavior of LDHs-FAS was further studied.
[0133] 4. Influencing factors
[0134] The pH value and ionic strength in actual wastewater may vary significantly, so it is crucial to study the adsorption changes of PFASs by LDHs-FAS under different pH and ionic conditions. Figure 5 The adsorption and removal efficiency of PFOS by LDHs-FAS under different environmental conditions in the examples; Figure 5 a in the figure is the adsorption and removal efficiency of PFOS by LDHs-FAS under different pH conditions. Figure 5 b in the figure is the adsorption and removal efficiency of PFOS by LDHs-FAS under different ionic strength conditions. Figure 5Where c is the adsorption and removal efficiency of PFOS by LDHs-FAS under different coexisting anions (such as chloride, nitrate, sulfate and carbonate).
[0135] like Figure 5 As shown in a, the adsorption removal rate of PFOS by LDHs-FAS was relatively stable in the range of pH 3 to 11. LDHs showed a lower adsorption capacity at pH 3, mainly due to its poor acid stability at this pH level.
[0136] In addition, under low pH conditions, fluorinated LDHs-FAS can form hydrogen bonds with the carboxylate and sulfonate head groups of PFOA and PFOS, thereby enhancing their adsorption capacity. - The concentration of ions also increases. Since PFOS exists in the form of anions in the water environment, OH - The ions may compete with PFOS for binding sites and metal nodes on LDHs. Overall, LDHs-FAS showed higher removal efficiency and stability in this pH range compared with unmodified LDHs. Figure 5 Figure b shows the effect of ionic strength on the adsorption of PFOS by the two materials. Within the range of NaNO3 concentrations studied, the removal efficiency of LDHs-FAS remained stable, while the removal efficiency of unmodified LDHs decreased significantly with increasing ionic strength. This suggests that at high ionic strength, an electrostatic shielding effect may occur on the adsorbent surface, which is not conducive to the adsorption of pollutants in water, further highlighting the importance of electrostatic effects in PFOS adsorption. The increase in ionic strength compresses the electrical double layer on the positively charged surface of LDHs, thereby reducing the electrostatic attraction between PFOS and unmodified LDHs. Similarly, previous studies have shown that an increase in salinity significantly reduces the adsorption of PFOS on various LDHs, while an increase in ionic strength has little effect on the removal of PFOS by fluorinated LDHs, maintaining a removal efficiency of nearly 90% even at an ionic strength of up to 50mM.
[0137] Studies have shown that increasing ionic strength enhances the hydrophobic interactions between organic pollutants and adsorbents. This effect can reduce surface tension and change the arrangement of PFAS on the adsorbent surface, thereby strengthening the interaction between the adsorbent and the hydrophobic tails of PFAS. Further studies characterized the hydrophobic properties of fluorinated and non-fluorinated LDHs by measuring water and oil contact angles ( Figure 1(c) and (d) in the figure). The water contact angle of LDHs-FAS (36.54°) is significantly higher than that of LDHs (0°), and this enhancement is caused by the presence of fluorine atoms, which reduce the surface energy and thus endow LDHs-FAS with higher hydrophobicity. Although the fluorinated organic part of LDHs-FAS is hydrophobic, the inorganic metal part (metal oxide cluster) is hydrophilic. Therefore, the entire LDHs-FAS does not show a high water contact angle. When the electrostatic interaction is suppressed, the hydrophobic interaction between LDHs-FAS and PFOS also contributes significantly to the ultra-high adsorption and removal efficiency of PFOS by LDHs-FAS. On the other hand, since the CF chain of PFOS is longer than that of PFOA, PFOS is more likely to form a micelle effect at the studied concentration, so that one adsorption site on LDHs-FAS can adsorb micelles containing multiple PFOS molecules. In addition, the CF chain of PFAS can extend into the bubble, and the CF chain of PFOS is more likely to concentrate on the bubble interface, thereby promoting the adsorption of PFOS on LDHs-FAS. Figure 4-1 The results of a and b in Figures 2 and 3 confirm the excellent removal effect of LDHs-FAS on PFOS and PFOA. In addition, the CF chains grafted onto LDHs-FAS can adsorb PFAS through fluorinophilic interaction. The CF chains of PFOS can be directly adsorbed onto the CF chains of LDHs-FAS, while the ionic ends of PFOS can be adsorbed onto the positively charged surface of LDHs. These results further indicate that in addition to the main anion exchange and hydrophobic interaction between PFOS and LDHs, fluorinophilic interaction may also be involved in the adsorption process of PFOS on LDHs-FAS.
[0138] The aqueous environment is complex in nature and usually contains various anionic species, which may adversely affect the adsorption process. Studies have also reported the effects of competing anions on the adsorption of oxygen anions by LDHs. Therefore, it is essential to explore the selectivity and stability of the synthesized LDHs-FAS by studying the effects of coexisting anions on the adsorption of PFOS in aqueous solution. Figure 5 The adsorption and removal efficiency of PFOS by LDHs-FAS under different environmental conditions in the examples; Figure 5 a in the figure is the adsorption and removal efficiency of PFOS by LDHs-FAS under different pH conditions. Figure 5 b in the figure is the adsorption and removal efficiency of PFOS by LDHs-FAS under different ionic strength conditions. Figure 5 Where c is the adsorption and removal efficiency of PFOS by LDHs-FAS under different coexisting anions (such as chloride, nitrate, sulfate and carbonate).
[0139] The interfering anions used in the experiment included chloride, nitrate, sulfate, and carbonate with an initial concentration of 1 mM. Figure 5 c in the figure shows that the presence of coexisting interfering anions significantly affected the adsorption process of PFOS and reduced the removal efficiency. Among them, the presence of monovalent anions such as chloride ions and phosphate ions slightly reduced the adsorption performance of LDHs, but had little effect on the adsorption performance of LDHs-FAS. It was also observed that divalent anions had a more significant interference effect than monovalent anions. In the presence of divalent sulfate ions and carbonate ions, the removal efficiency of PFOS by LDHs decreased significantly, by 68.91% and 80.55%, respectively. PFOS exists in the form of anions in water environments, such as Figure 1 c and e in Figure 2 The zeta potential and water contact angle results of c in Fig. 3 indicate that the unmodified LDHs have a positively charged structure and hydrophilicity, and thus may adsorb PFOS through electrostatic interaction. However, LDHs-FAS only showed a decrease in PFOS removal efficiency of 16.31% and 12.37%, maintaining an adsorption rate of more than 80%, respectively, which is 309% and 584% of the efficiency of unmodified LDHs for PFOS adsorption. This can be explained by the ionic radius, strong affinity, and electronegativity of the adsorbent. Studies have shown that the positively charged structure of LDHs has a higher affinity for divalent anions than for monovalent anions. Divalent anions such as sulfate and carbonate ions may bind to the positively charged surface of LDHs through electrostatic attraction, thereby strongly inhibiting the adsorption of PFOS in the presence of these anions. In contrast, the synthesized LDHs-FAS is a multifunctional adsorbent, which may be due to the hydrophobic interaction and fluorophilic interaction caused by its surface-modified organic functional groups and fluorinated functional groups, which enhances its affinity and selectivity for PFOS adsorption. It can effectively and stably remove PFOS from water even when the reaction mixture contains competing anions.
[0140] 4. Removal of various PFOS
[0141] Since many PFASs may coexist in contaminated source water, it is important to evaluate the removal performance of LDHs-FAS for PFOS in the presence of PFAS mixtures. The present invention investigated a mixture of 11 PFASs with different structures and fluoroalkyl chain lengths, including five PFCAs, three PFSAs, F-53B, 6:2FTTS, and HFPO-TA. Even in the presence of 11 PFASs, LDHs-FAS still showed a 95% removal efficiency for PFOS (e.g. Figure 6 ). Figure 6 This is a diagram showing the removal effect of LDHs-FAS prepared in the example on a PFAS mixture.
[0142] Figure 6 It was shown that LDHs-FAS performed better in removing long-chain PFASs, while its ability to remove short-chain PFASs decreased. In addition, the adsorption capacity of carboxylate and sulfonate compounds increased regularly with the increase in chain length. The adsorption capacity of perfluorosulfonates was higher than that of perfluorocarboxylates of the corresponding carbon number, which was attributed to the stronger hydrophobicity of perfluorosulfonates. Although perfluorosulfonates and perfluorocarboxylates have the same number of carbons (PFBA vs. PFBS, PFHxA vs. PFHxS, PFOA vs. PFOS), perfluorosulfonates exhibit stronger hydrophobicity due to the additional tail carbon (longer CF chain). The reduced removal efficiency of short-chain PFASs may be related to their shorter CF chains and their low hydrophobicity relative to other PFASs in the mixture. Therefore, long-chain PFAS may replace short-chain PFBA when competing for adsorption sites in solution, emphasizing the importance of hydrophobic interactions in the adsorption process. LDHs-FAS was able to remove more than 90% of PFOS, PFDA, F-53B, and HFPO-TA, and its performance was superior to that of unmodified LDHs. The results showed that the adsorption performance of LDHs-FAS in water was good overall, and it could maintain a high removal efficiency for the target pollutant PFOS even in the presence of multiple PFASs. In addition, LDHs-FAS was also able to remove various long-chain anionic PFASs. The competitive adsorption of PFASs on LDHs-FAS depended on their ionic head groups and CF chains. Sulfonic acid PFASs with sulfonate groups and long CF chains were preferentially adsorbed on LDHs-FAS. They exerted synergistic effects through hydrophobic interactions and fluorine-philic effects, enhancing the total adsorption capacity in the mixed system. Overall, LDHs-FAS is a suitable candidate adsorbent for the removal of long-chain PFASs.
[0143] 5. Regeneration and reuse of LDHs-FAS
[0144] In addition, the regeneration of spent adsorbents is one of the key issues in the adsorption process. It has been reported that the use of organic solvents or inorganic salts alone cannot effectively and completely desorb PFASs from spent resins because the adsorption process involves anion exchange and hydrophobic interaction.
[0145] Therefore, the present invention regenerates the waste LDHs-FAS adsorbing PFOS in a mixed solution containing methanol and sodium chloride at different concentrations. Figure 7 This is a graph showing the regeneration and reuse performance of LDHs-FAS prepared in the example; Figure 7 a in the figure is a comparison of the effects of regenerating LDHs-FAS saturated with PFOS using mixed solutions of methanol and NaCl at different concentrations. Figure 7 b in the figure is the adsorption performance of LDHs-FAS on PFOS in three adsorption-desorption cycles. Figure 7As shown in a, all three mixtures containing methanol and sodium chloride can effectively elute PFOS from the adsorbent, and the amount of PFOS desorbed increases accordingly with the increase of methanol concentration. It is worth noting that in the first cycle, the amount of PFOS adsorbed on LDHs-FAS is relatively small, which may be due to the electrostatic repulsion and fluorine-philic attraction of the newly introduced anionic sulfonic acid groups and CF chains on LDHs-FAS, resulting in some unavailable adsorption sites. The adsorption of PFOS is stable in subsequent reuse cycles. The mixture containing 70% methanol and sodium chloride is superior to the other two mixtures in desorption and regeneration of PFOS. The mixture of methanol and sodium chloride can effectively elute PFOS from the material because the CF chains in PFOS can extend into the nanobubbles, thereby eliminating the bubbles on the adsorbent and facilitating the regeneration of the spent adsorbent. Methanol helps to remove the bubbles attached to the CF chains of LDHs-FAS and weakens the hydrophobic interaction between PFOS and LDHs-FAS, thereby promoting the desorption of PFOS. Chloride ions promote the desorption of PFOS from LDHs and its redissolution in methanol. Subsequently, the LDHs-FAS adsorbed with PFOS is regenerated using a mixed regeneration solution of sodium chloride and methanol ( Figure 7 b), it was observed that the LDHs-FAS regenerated in all mixed solutions maintained a PFOS removal rate of more than 95% in three adsorption cycles. These results indicate that LDHs-FAS may be an efficient and robust adsorbent that can be used multiple times for the removal of PFOS. In summary, the present invention provides an efficient, economical, and environmentally friendly water treatment material suitable for removing PFASs from groundwater and industrial wastewater, providing a new approach to solving the PFASs pollution problem.
[0146] Example 2
[0147] The preparation method is basically the same as that in Example 1, except that the addition amount of 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 0 mL / g.
[0148] Example 3
[0149] The preparation method is basically the same as that in Example 1, except that the addition amount of 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 0.2 mL / g.
[0150] Example 4
[0151] The preparation method is basically the same as that in Example 1, except that the addition amount of 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 0.4 mL / g.
[0152] Example 5
[0153] The preparation method is basically the same as that in Example 1, except that the addition amount of 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 0.6 mL / g.
[0154] Test Case
[0155] (1) Experimental study on the adsorption and removal of PFOS by LDHs-FAS prepared by coprecipitation in Examples 1 to 5 of the present invention is shown in Table 3. When preparing LDHs-FAS in Examples 1 to 5, the addition amounts of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane were 0 mL / g, 0.1 mL / g, 0.2 mL / g, 0.4 mL / g and 0.6 mL / g, respectively. The present invention uses the LDHs-FAS adsorbent prepared in Examples 1 to 5 to study PFOS adsorption, sets the PFOS concentration to 1 mg / L, the initial pH value to 7, and the adsorbent dosage to 0.25 g / L. A 24-hour adsorption equilibrium experiment is conducted under the conditions of a constant temperature shaker at 160 rpm and 25°C. The results show that the LDHs-FAS with an addition amount of 0.1 mL / g of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane has the best removal effect on PFOS (the removal rate of the target product obtained with an addition amount of 0.1 mL / g of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane in Example 1 is 97.21%). This shows that the LDHs-FAS prepared in Examples 1 to 5 exhibits a rapid removal effect and ultra-high adsorption capacity for PFOS, and can be used as a promising adsorbent for PFAS remediation in water bodies.
[0156] Table 3 Removal effect of PFOS by LDHs-FAS prepared by coprecipitation in Examples 1 to 5
[0157]
[0158]
[0159] (2) The present invention uses the LDHs and LDHs-FAS adsorbents prepared in Example 1 to study the adsorption of different types of PFAS, wherein the PFAS include perfluorobutyric acid (PFBA), perfluoropentanoic acid (PFPeA), perfluorohexanoic acid (PFHxA), perfluorooctanoic acid (PFOA), perfluorodecanoic acid (PFDA), perfluorobutane sulfonic acid (PFBS), perfluorohexane sulfonic acid (PFHxS), perfluorooctane sulfonic acid (PFOS), 6:2 fluoro-tween sulfonic acid (6:2FTS), perfluoroalkyl ether sulfonate (F-53B) and hexafluoropropylene oxide trimer acid (HFPO-TA). The test method is: the concentration of each type of PFAS in the mixed solution is set to 200 μg / L, the initial pH value is 7, the amount of adsorbent is 0.25 g / L, the adsorption equilibrium experiment is carried out under the condition of a constant temperature shaker at 25°C, and the concentration of each PFAS after adsorption equilibrium is measured by liquid chromatography-tandem mass spectrometry.
[0160] The test results are as follows Figure 6 And as shown in Table 4. Figure 6 Table 4 is a comparison of the removal rates of different types of PFASs mixed solutions by LDHs and LDHs-FAS prepared in Example 1 of the present invention. Figure 6 As shown in Table 4, the LDHs-FAS prepared in Example 1 of the present invention has a higher removal effect on 12 PFAS than LDHs, among which the removal effect on short-chain PFAS such as fluorobutyric acid (PFBA), perfluoropentanoic acid (PFPeA), perfluorohexanoic acid (PFHxA), and perfluorobutane sulfonic acid (PFBS) is significantly improved, and the removal rate of long-chain PFAS such as perfluorooctanoic acid (PFOA), perfluorodecanoic acid (PFDA), perfluorohexane sulfonic acid (PFHxS), perfluorooctane sulfonic acid (PFOS), 6:2 fluorosulfonic acid (6:2FTS), perfluoroalkyl ether sulfonate (F-53B) and hexafluoropropylene oxide trimer acid (HFPO-TA) is very high (>91.5%).
[0161] Table 4 Comparison of the removal efficiency of LDHs and LDHs-FAS prepared in Example 1 on mixed solutions of different types of PFASs
[0162]
[0163]
[0164] From the above examples, it can be seen that the method provided by the present invention mixes an inorganic strong base, a water-soluble aluminum salt, a water-soluble divalent metal salt and water, and performs a coprecipitation reaction under the condition of pH value>10. The obtained coprecipitation product is dispersed in ethanol and aged at room temperature to obtain the fluorinated functional layered double metal hydroxide. The present invention only uses ethanol as a reaction solvent, and prepares the fluorinated functional layered double metal hydroxide by a simple one-pot method at room temperature. The obtained fluorinated functional layered double metal hydroxide has high purity and high yield, while reducing the production cost, being more green and environmentally friendly, and suitable for industrial production. And the fluorinated functional layered double metal hydroxide provided by the present invention shows a rapid removal effect and ultra-high adsorption capacity for perfluoro or polyfluoroalkyl substances, and can be used as a promising adsorbent for the remediation of PFASs in water bodies.
[0165] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A fluorosilane coupled layered double metal hydroxide composite material, characterized in that: The invention comprises a layered double metal hydroxide and a fluorosilane coupling agent which is chemically modified on the surface of the layered double metal hydroxide.
2. The fluorosilane coupled layered double hydroxide composite material according to claim 1, characterized in that: The layered double metal hydroxide includes a magnesium-aluminum type layered double metal hydroxide.
3. The fluorosilane coupled layered double hydroxide composite material according to claim 1 or 2, characterized in that: The fluorosilane coupling agent includes 1H,1H,2H,2H-perfluorooctyltriethoxysilane.
4. The method for preparing the fluorosilane coupled layered double metal hydroxide composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The layered double metal hydroxide, alcohol solvent, fluorosilane coupling agent and catalyst are mixed to carry out coupling reaction to obtain the fluorosilane coupled layered double metal hydroxide composite material.
5. The preparation method according to claim 4, characterized in that: The volume ratio of the layered double metal hydroxide to the fluorosilane coupling agent is 1 g: (0.1-0.6) mL.
6. The method according to claim 4 or 5, characterized in that: The alcohol solvent includes ethanol, the catalyst includes an organic acid, the coupling reaction temperature is room temperature, and the reaction time is 24 to 48 hours.
7. Use of the fluorosilane coupled layered double metal hydroxide composite material according to any one of claims 1 to 3 or the fluorosilane coupled layered double metal hydroxide composite material prepared by the preparation method according to any one of claims 4 to 6 in removing perfluoro or polyfluoroalkyl substances from water.
8. The use according to claim 7, characterized in that: The perfluoro or polyfluoroalkyl substance includes one or more of perfluorobutyric acid, perfluoropentanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, perfluorooctanoic acid, perfluorodecanoic acid, perfluorobutane sulfonic acid, perfluorohexane sulfonic acid, perfluorooctane sulfonic acid, 6:2 fluorosulfonic acid, perfluoroalkyl ether sulfonate and hexafluoropropylene oxide trimer acid.
9. The use according to claim 7 or 8, characterized in that: The pH value of the water body containing perfluoro or polyfluoroalkyl substances is 3 to 11; the ionic strength of the water body containing perfluoro or polyfluoroalkyl substances is 1 to 50 mM; the water body containing perfluoro or polyfluoroalkyl substances also contains coexisting ions, and the coexisting ions include one or more of nitrate ions, chloride ions, carbonate ions and sulfate ions.
10. The use according to claim 7, characterized in that: The application comprises the following steps: adding the fluorosilane coupled layered double metal hydroxide composite material to a water body containing perfluoro or polyfluoroalkyl substances for adsorption, thereby obtaining a water body from which the perfluoro or polyfluoroalkyl substances are removed and an adsorption-saturated fluorosilane coupled layered double metal hydroxide composite material; The adsorption saturated fluorosilane coupled layered double metal hydroxide composite material is regenerated, and the regeneration is performed using a regeneration solution, and the regeneration solution includes methanol, NaCl and water.
Citation Information
Cited By
Method for detecting short-chain / ultra-short-chain PFAS in multiple environmental media of surface water-underground water interaction system
CN119915924A
Hydrotalcite-like derived oxide modified charcoal catalyst, preparation method and application thereof in deacidification of industrial flue gas
CN120242994A